The use of orthopedic surgical devices for forensic identiﬁcation: A systematic review - Bukhamseen, Abrar H.; Aldhameen, Abrar A.; Alzayyat, Nof T.; Alqadeeb, Maria M.; Alotaibi, Bashair K.; Aljohani, Raghad I.; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Identification of human bodies is a necessary step in forensic practice. DNA analysis, fingerprints, and dental charting are considered conventional identification methods. However, these methods are not always applicable. Orthopedic surgical implantable devices provide valuable identity information when conventional methods of identification are not applicable or in challenging circumstances. This paper aims to review the usage of orthopedic implantable devices for forensic human identification.Methods: A search for relevant articles using the PubMed database in January 2021 identified 8 articles that met the inclusion criteria. Results: These articles highlighted the importance of the use of orthopedic implantable devices as an additional method for positive identification, especially in disaster situations. It is a method that needs antemortem and postmortem radiographs, comprehensive information of the orthopedic implantable device like company and serial number, logo, name, medical records of previous surgical intervention, and for the family member’s history to match with the identification details.Conclusions: Efforts should be made to include all information pertaining to orthopedic implantable devices in the medical records. Educating and training forensic experts on the use of such devices in the identification process is essential, as this technique is practical, low-cost, and time-saving.